Big Book Learning Media Improves the Moral Behavior of Early Childhood - Ardayani, Kadek Dian; Suarjana, I Made (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
Many children still do not understand moral behavior, such as the importance of saying thank you and being willing to forgive each other if they make mistakes. Thus, the moral development of children has not developed optimally. This study aims to produce Big Book media to improve children's moral behavior. The development model used in this research is the ADDIE model. The ADDIE model consists of analysis (analyze), design (design), development (development), implementation (implementation), and evaluation (evaluation). In this research, only up to the development stage. The validation of the Big Book media instrument was carried out by three experts, namely material experts and media experts. This study collected data using a questionnaire method to test the media and materials. This study obtained the Big Book media to improve the moral behavior of early childhood, which was declared valid based on expert tests with the CVR and CVI scores being 1.00. The form of the development of the big book media produced is a medium used to improve the moral behavior of early childhood. PAUD teachers can use this Big Book media to improve children's moral behavior.